The Reaction of the Colombian Catholic Church to the Secularization of Sexual and Reproductive Life (1960–1980). - Bastidas, Luis Bernardo; Beltrán, William Mauricio (Sexuality & Culture, 2019)
Although the Catholic Church has been, since Spanish colonization, the hegemonic religious institution in Colombia, it has lost control over different spheres of society including private life, especially since the second half of the twentieth century. Significant cultural changes, demographic growth, more access to education and work, the rise of mass media, legal advancement in women´s favor and the weakening of the pulpit and the confession as spaces of social control, led to the transformation of the ideas around sexuality and the traditional family model. This article aims to show how in Colombia, despite the strong opposition of the church and the efforts it made to maintain Catholic values, the reproductive and sexual sphere have managed to secularize, meaning it has accomplished autonomy. Today, this sphere is considered as something intimate and private, and the influence that Catholic Church had over it has declined.